Influencia de los medios audiovisuales (Ecuador tv y Tctelevisión) en los adolescentes de 12 a 16 años en la Ciudad de Babahoyo, Provincia de los Ríos - Albán Galeas, Jenny Marcela (2016)
The present research project contemplates a significant and contextualized work of the influence of the audiovisual media (Ecuador Tv and Tc Televisión) in the adolescents of 12 to 16 years in the city of Babahoyo, province of Los Ríos of 2016, with the main objective To determine the interest of educational and cultural information in young people. The aforementioned media were analyzed and it was determined that they have a grill of one hour a day in educational and cultural programming, at different times. But, in a survey conducted to the students of the College Annex of the Technical University of Babahoyo, reflected the little interest of young people in these issues, having as main information consumption sports. However, in surveys of parents of the campus, it was determined that most do not monitor the programming that their children consume leaving them vulnerable to receiving information of any kind and that does not contribute to the development of their personality. While in a field research carried out to local Social Communicators, they express that the shared educational and cultural contents in Ecuador Tv and Tc Television do not influence the behavior of young people because they are very linear and do not allow interaction with the current adolescents, More dynamic and entertaining programs. Conclusions and recommendations of the work investigated were offered in addition to the proposal of a script for an educational and cultural program directed to the students of the city of Babahoyo and general public